Problems regarding emergency ultrasound in Nepal - Joshi, BR; Pradhan, S; Ansari, MA (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: Ultrasound plays an important role in management of emergency patients. This study was performed to define the patterns of indications and to analyze the findings. Materials and Methods: Hundred patients were analyzed for 6 months from 15th August 2003. Results: Females were 59 percent. Thirty-nine percent were of 20-29 years age group. Eleven percent presented during 8-9 PM . Provisional diagnosis and clinical history were not mentioned in some requisition forms. Normal findings were present in 18 %. Normal pregnancy was present in 11%. Acute appendicitis was present in 9%. Two were positive for ectopic pregnancy. Conclusion: Ultrasound should be used as complementary investigation and not instead of clinical examination. Keywords: Emergency, ultrasound, appendicitis Journal of Institute of Medicine, April, 2008; 30:1 2-5 The full text of this paper is available from the Journal of Institute of Medicine website